NEW RESEARCH ON ROMANI IN EASTERN NORTH MACEDONIA: THE MALESHEVO DIALECT (Journal of Contemporary Philology, 2025)
This article presents new data on previously undescribed Romani varieties spoken in the eastern part of the Republic of North Macedonia, specifically in the geographical region of Maleshevo. We show that this is a South Balkan dialect that differs from other South Balkan dialects spoken in North Macedonia (especially in Skopje), while sharing several features with the Romani dialects of southwestern Bulgaria. This pattern corresponds to the geographical distribution of South Slavic dialects. Following South Slavic terminology, these Romani varieties can be referred to as Maleshevo-Pirin Romani. In addition to describing typical dialectal features, this study pays special attention to borrowings from local Macedonian dialects.
Keywords: Romani; Macedonian; dialectology; language contact